EKSPLORASI PERAN ORGANIZATIONAL SUPPORT DAN PROACTIVE COPING TERHADAP KINERJA KARYAWAN GENERASI Z - Djunaedi Djunaedi; Ana Fitriyatul Bilgies; Tanti Widia Nurdiani; Darwis Darwis; Haniwijaya Pahlawansah; Vivid Violin (JURNAL LENTERA BISNIS, 2025)
Generation Z is starting to dominate the world of work and presenting new challenges in human resource management. This study aims to explore the role of organizational support and proactive coping on the performance of Generation Z employees. Organizational support plays a role in providing support that can improve employee well-being and productivity. At the same time, proactive coping is a strategy that allows individuals to overcome work challenges more effectively. This study uses a quantitative method with a survey approach involving 250 respondents from industrial sectors. Data were collected through questionnaires that have been tested for validity and reliability. The analysis results show that organizational support positively influences the performance of Generation Z employees, both directly and through increasing proactive coping. In addition, proactive coping also acts as a mediator in the relationship between organizational support and employee performance. Thus, organizations need to increase support for employees and encourage the development of proactive coping strategies to improve their performance. The implications of this study are expected to provide insight for HR practitioners in designing more effective work policies and programs for Generation Z employees.